Comparison of local ablation with Albendazole or laparoscopic hepatectomy combined with Albendazole in the treatment of early hepatic alveolar echinococcosis - Jide A; Jinping Chai; Zongping Shao; Shunyun Zhao; Hao Wang; Xiangren A; Xiangren A; Xiangren A; Jinyu Yang (Frontiers Media S.A., 2022)
BackgroundEchinococcosis (E) is a zoonotic parasitic disease caused by the larval morphology of echinococcosis tapeworms. Among the recognized species, two are of medical importance-E. granulosus and E. multilocularis-causing cystic echinococcosis (CE) and alveolar echinococcosis (AE) in humans, respectively. Diagnosis of AE is based on clinical manifestation and epidemiological data, imaging techniques, histopathology and/or nucleic acid detection, and serology. At present, WHO guidelines suggest that benzimidazoles (BMZ) are mandatory in all AE patients, temporarily after complete resection of the lesions and for life in all other AE cases. Interventional procedures should be preferred to palliative surgery whenever possible, and radical surgery is the first choice in all cases suitable for total resection of the lesion. However, some research centers have proposed that local ablation (LA) including radiofrequency ablation (RFA) and microwave ablation (MWA) is no less effective than radical surgery or better than simple medication in the early stage hepatic AE (WHO-IWGE PNM classification of AE: P1N0M0). This study attempted to compare the real efficacy of the above treatment methods, so as to find the best treatment for this kind of patient.MethodsThe data of patients with hepatic AE who underwent laparoscopic hepatectomy (LH), RFA, and MWA in Qinghai Provincial People's Hospital from January 2015 to January 2021 were collected. At the same time, the cases treated with Albendazole (ABZ) were collected together with the institution for disease control and prevention. According to the treatment methods, the above cases were divided into LH group, RFA group, MWA group, and medication group. The basic data and postoperative recovery indices of the four groups were compared, respectively.ResultsA total of 199 patients with hepatic AE were enrolled in this study, including 90 males and 109 females. The youngest was 5 years old and the oldest was 66 years old, with an average of 33.41±14.64 years old. 20.6% of the patients had hepatitis B (41/ 199). A total of 45 patients underwent ultrasound-guided RFA, 47 patients underwent ultrasound-guided MWA, 51 patients were treated with ABZ, and 56 patients underwent LH. There were no significant differences in baseline characteristics among the four groups (p > 0.05). The RFA group and MWA group were more advantageous than the LH group regarding operation time and incidence of postoperative complications (p < 0.05). But recurrence rate of the lesion in the LH group was significantly lower than the RFA group, MWA group, and medication group. However, there was no significant difference in recurrence-free survival time among the four groups (p >0.05).ConclusionLH has a significant effect in the treatment of early-stage hepatic AE, especially in terms of recurrence which is significantly better than LA and medication alone. Follow-up and adherence to ABZ therapy are essential if conservative treatment is to achieve better outcomes.